Perbandingan Kejadian Dismenore Pada Akseptor Pil KB Kombinasi Dengan Akseptor Suntik KB 1 Bulan DiWilayah Kerja Puskesmas Pasayangan - Noor, Meitria Syahadatina; Yasmina, Alfi; Di Hanggarawati, Connyvera (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2010)
More than 50% women who have menstruations will get dysmenorrheal occurrence. Dysmenorrhea is a typeof pain in the stomach that originates from uterine cramps in the menstrual period. Using the oralcontraceptive and monthly injected contraceptive can reduce dysmenorrhea occurrence. The aim of the studywas to find out the difference of dysmenorrheal occurrence between the oral contraceptive users and monthlyinjected contraceptive users in Pasayangan Public Health Center. It was an analytic observational study withcross-sectional design. Sample were chosen by purposive sampling technique. Subjects in this research were30 oral contraceptive users and 30 monthly injected contraceptive users in Pasayangan Public Health Center.The dysmenorrheal occurrence was assessed with questionnaire. The result of the research indicated thatdysmenorrheal occurrence were suffered more by oral contraceptive users (8 subjects), while only 1 bymonthly injected contraceptive users. Analysis with Fisher’s Exact Test gave p value of 0.026 (p < 0.05),hence it could be concluded that dysmenorrheal occurrence in monthly injected contraceptive users weresignificantly lower than those in oral contraceptive users.Keywords: dysmenorrhea, oral contraceptive, monthly injected contraceptivehttp://ejournal.undip.ac.id/index.php/mkmi/article/view/2818